Pemanfaatan daun kelor (Moringa Leifra) dalam fortifikasi pembuatan nugget - Matondang , Syaiful Nasri; Asmaq, Nur (Journal of Pharmaceutical and Sciences, 2024)
The aim of this research was to determine the quality of chicken nuggets by adding moringa leaf flour (Moringa leifra) in the manufacturing process. The materials used in this research were broiler chicken meat, Moringa leaf flour, wheat flour, bread flour, eggs, tapioca flour, shallots, garlic, oil, pepper, salt and other kitchen spices. The method used in this research was an experimental method with a completely randomized non-factorial design with 4 treatments and 4 replications. The parameters tested were Antioxidants, Cholesterol, and Total Bacterial Colonies. The treatments in this study were P0 (without the addition of Moringa leaves); P1 (addition of 5% Moringa leaf flour); P2 (addition of 10% Moringa leaf flour), P3 (Addition of 15% Moringa leaf flour). The results of this study showed that the addition of Moringa leaf flour in making chicken nuggets had a very significant effect (P<0.01) on antioxidant and cholesterol levels.